Culinary strategies to manage glycemic response in people with type 2 diabetes: A narrative review - Murillo, Serafin; Mallol, Ariadna; Adot, Alba; Juárez, Fabiola; Coll, Alba; Gastaldo, Isabella; Roura, Elena (Frontiers in Nutrition, 2022)
Diet plays a critical role in the management of many chronic diseases. It is well known that individuals with type 2 diabetes need to pay close attention to foods rich in carbohydrates to better manage their blood sugar. Usually, individuals are told to increase their dietary fiber intake which is associated with better glycemic control and limit their overall carbohydrate consumption. However, there are many other cooking strategies available to reduce the glycemic response to meals rich in carbohydrates and with a high glycemic index, such as adding fats, proteins, or vinegar, modifying the cooking or preparation processes, and even the selection and storage of foods consumed. The aim of the present narrative review is to summarize some of these existing strategies applied to the cooking process and their ability to modulate glycemic response to meals in individuals with type 2 diabetes.